Evaluation of the therapeutic efficacy of praziquantel against schistosomes in seven countries with ongoing large-scale deworming programs. (December 2020) - Levecke, B.; Vlaminck, J.; Andriamaro, L.; Ame, S.; Belizario, V.; Degarege, A.; Engels, D.; Erko, B.; Garba, A.D.; Kaatano, G.M.; Mekonnen, Z.; Montresor, A.; et al.
Abstract: The World Health Organization (WHO) recommends periodic assessment of the therapeutic efficacy of praziquantel (PZQ) to detect reduced efficacy that may arise from drug resistance in schistosomes. In this multi-country study (2014), we assessed the therapeutic efficacy of a single oral dose of PZQ (40 mg/kg) against Schistosoma mansoni (Brazil, Cameroon, Ethiopia, Mali, Madagascar and Tanzania), S. haematobium (Cameroon, Ethiopia, Mali, Tanzania and Zanzibar) and S. japonicum (the Philippines) infections in school-aged children, across a total of 12 different trials. Each trial was performed according to the standardized methodology for evaluating PZQ efficacy as described by the WHO. Overall, therapeutic efficacy, measured as the reduction in arithmetic mean of schistosome egg counts following drug administration (egg reduction rate; ERR), was high for all three schistosome species ( S. mansoni : 93.4% (95%CI: 88.8–96.8); S. haematobium : 97.7% (95%CI: 96.5–98.7) and S. japonicum : 90.0% (95%CI: 68.4–99.3). At the trial level, therapeutic efficacy was satisfactory (point estimate ERR ≥90%) for all three Schistosoma species with the exception of S. mansoni in Cameroon where the ERR was 88.5% (95%CI: 79.0–95.1). Furthermore, we observed that in some trials individual drug response could vary significantly (wide 95%CI) and that few non-responsive individuals could significantly impact ERR point estimates. In conclusion, these results do not suggest any established reduced efficacy of the standard PZQ treatment to any of the three schistosome species within these countries. Nevertheless, the substantial degree of variation in individual responses to treatment in some countries underpins the need for future monitoring. The reported ERR values serve as reference values to compare with outcomes of future PZQ efficacy studies to ensure early detection of reduced efficacies that could occur as drug pressure continues increase. Finally, this study highlights that 95%CI should be considered in WHO guidelines to classify the therapeutic efficacy of PZQ. Graphical abstract: Image 1 Highlights: PZQ efficacy against schistosomes was assessed in school-aged-children in seven countries. There was no overall sign of reduced PZQ efficacy against any schistosome species. Notable variation in individual responses to treatment does require future monitoring. It is recommended to include reporting of the 95%CI in future WHO guidelines.